Load Monitoring Methods for Controlling Training Effectiveness on Physical Conditioning and Planning Involvement: A Narrative Review - Macedo, Anderson G. [UNESP]; Almeida, Tiago A. F. [UNESP]; Massini, Danilo A. [UNESP]; de Oliveira, David M.; Espada, Mário C.; Robalo, Ricardo A. M.; Hernández-Beltrán, Víctor; Gamonales, José M.; Vilela Terra, Andréia M. S.; Pessôa Filho, Dalton M. [UNESP] (MDPI, 2024)
Monitoring the training load during training is important for quantifying the demand on psychological and physiological responses. This procedure is achieved through subjective and objective methods applied to the control of the level of training, to the attainment of conditioning and performance goals, and to the prevention of injuries. Training load refers to either external load, such as the variables of speed, distance, accelerations, and decelerations, or internal load, which is related to the psychological and physiological responses during an exercise session or training period (e.g., rating of perceived exertion—RPE; and heart rate—HR). To measure external load, traditional methods include pedometers, accelerometers, global positioning systems, and volume load. For internal load, methods include RPE, training monotony, strain, and impulse, HR, hormonal and biochemical markers, and training diaries and questionnaires. The current review reinforces the assumption that the methods should be combined to improve confidence with the information, mainly when assessing internal load stress during training. Moreover, training load provides an objective assessment of performance levels and involvement in different training phases, thus providing relevant information to analyse strategies for the effectiveness of conditioning progress, performance enhancement, and injury prevention.
Keywords: performance; performance indicators; rating of perceived exertion; workload